Structure-Guided Discovery of cis-Hexahydro-pyrido-oxazinones as Reversible, Drug-like Monoacylglycerol Lipase Inhibitors - Kuhn, Bernd; Ritter, Martin; Hornsperger, Benoit; Bell, Charles; Kocer, Buelent; Rombach, Didier; Lutz, Marius D. R.; Gobbi, Luca; Kuratli, Martin; Bartelmus, Christian; Bürkler, Markus; Koller, Raffael; et al. (Journal of medicinal chemistry, 2024)
Monoacylglycerol lipase (MAGL) is a key enzyme involved in the metabolism of the endogenous signaling ligand 2-arachidonoylglycerol, a neuroprotective endocannabinoid intimately linked to central nervous system (CNS) disorders associated with neuroinflammation. In the quest for novel MAGL inhibitors, a focused screening approach on a Roche library subset provided a reversible benzoxazinone hit exhibiting high ligand efficiency. The subsequent design of the three-dimensional cis-hexahydro-pyrido-oxazinone (cis-HHPO) moiety as benzoxazinone replacement enabled the combination of high MAGL potency with favorable ADME properties. Through enzymatic resolution an efficient synthetic route of the privileged cis-(4R,8S) HHPO headgroup was established, providing access to the highly potent and selective MAGL inhibitor 7o. Candidate molecule 7o matches the target compound profile of CNS drugs as it achieves high CSF exposures after systemic administration in rodents. It engages with the target in the brain and modulates neuroinflammatory processes, thus holding great promise for the treatment of CNS disorders.